2020
DOI: 10.5897/ajar2020.14917
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of the contamination of exported sesame by Salmonella species from 2007 to 2017 in Burkina Faso

Abstract: Sesame (Sesamum indicum) is one of the oldest and most traditional oilseed crops, valued for its highquality seed oil. This culture was introduced in Burkina Faso at the beginning of the 20th century where it occupies a place of cash crop. The majority of sesame produced in Burkina Faso is export oriented. However, the contamination by Salmonella remains an unsolved problem. This retrospective study was carried out in order to assess the microbiological safety of sesame samples received at the Laboratoire Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In developing countries such as Burkina Faso, numerous studies have previously reported the presence of Salmonella spp. in RTE foods [30][31][32]. Te potential hygiene breakdowns at various stages of the food processing and distribution chain due to the lack of food safety regulations and food handler educations are responsible for food contamination in developing countries [33].…”
Section: Presumptive Salmonella Isolates and Molecularmentioning
confidence: 99%
“…In developing countries such as Burkina Faso, numerous studies have previously reported the presence of Salmonella spp. in RTE foods [30][31][32]. Te potential hygiene breakdowns at various stages of the food processing and distribution chain due to the lack of food safety regulations and food handler educations are responsible for food contamination in developing countries [33].…”
Section: Presumptive Salmonella Isolates and Molecularmentioning
confidence: 99%